Chemical composition of Bakken crude oil burn residue: Environmental relevance following train derailment fires. Issue 3 (14th August 2020) - Stout, Scott A.
Abstract: Shipments of Bakken crude oil by rail have increased in concert with the production of unconventional crude oil in the Williston Basin over the past 10 years, during which time multiple fiery train derailments resulted in tragic loss of life and/or environmental impacts. In this study the compositions of Bakken oil burn residues from a derailment fire(s) are compared to fresh and laboratory-evaporated Bakken crude oil. The absolute and hopane-normalized concentrations of n- alkanes, unsubstituted and substituted PAHs, and petroleum biomarkers and their percent depletions and enrichments (relative to hopane) are reported. Bakken oil burn residues lost 67–78% of their total chromatographable mass (C5 to C44 ) and exhibit chemical trends distinct from naturally-evaporated oil, including (1) the shape of their UCM profiles, (2) depletion of n -alkanes up to (at least) n -C30, (3) enrichment of priority pollutant (pyrogenic) PAHs, specifically favoring PAH isomers containing three or more linear aromatic rings (anthracene or benz[ a ]anthracene) or 5-member rings (fluoranthene or indeno[ 1, 2, 3-c, d ]pyrene), and (4) depletion of some lower boiling petroleum biomarkers (C23 -C25 tricyclic terpanes). Despite relative enrichment of most priority pollutant PAHs the absolute concentrations of both total PAH (TPAH50 ) and priority pollutant PAH (PPAH16 ) in the burn residues were depleted 69–78% and 41–48%, respectively, compared to fresh Bakken oil. These results demonstrate the changes and range of compositions among fresh, evaporated, and variably-combusted residues of Bakken crude oil, the latter of which are important in assessing the potential effect(s) of burn residues on the environment proximal to train derailment fires.